Utilizing Cow Manure Waste (Bos Taurus) as Organic Fertilizer in Labuan Lelea Village, Labuan District, Donggala Regency, Central Sulawesi - Arifuddin Lamusa; Ali Akrab (International Journal Of Community Service, 2024)
This community service activity has been conducted in Labuan Lelea Village, Labuan District, Donggala Regency, Central Sulawesi Province, in collaboration with the local farming community. They face challenges regarding how to utilize cattle manure waste as environmentally friendly organic fertilizer. The objective of this community service is: 1) To provide knowledge to the farming community in Labuan Lelea Village on how to utilize cattle manure waste as organic fertilizer, as a substitute for inorganic fertilizers, which are known for their chemical content, scarcity, and fluctuating prices annually; 2) To promote organic fertilizers as an environmentally friendly alternative to inorganic fertilizers in agricultural lands; 3) To enhance the knowledge of farming communities regarding the effective utilization of cattle manure waste as organic fertilizer for both food crops and horticultural plants. The method employed in this activity is a participatory approach, wherein a team including Community and Student Service Learning Program (KKN) participants and local community members actively collaborate in fostering good cooperation between extension workers and farmers. The primary target audience of this training is farming communities engaged in plantation, food crops, and horticultural cultivation. The outcomes of this community service activity include increased awareness of how to utilize cattle manure waste (Bos Taurus). This process requires minimal investment as cattle waste, sawdust, and rice husks are all freely available materials, thus serving as a substitute for inorganic fertilizers which contain chemical substances and are environmentally unfriendly.